Development of UI/UX Application of Javanese Script Using User Centered Design in Elementary School - Wibowo, Adlan; Rakhmawati, Desty; Ikhsan, Ali Nur (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Indonesia is a country with an area of 1.9 million km², rich in diversity, including various languages in each region. This linguistic diversity gives each region its unique characteristics. However, in the 21st century, there is a noticeable decline in the use of regional languages, particularly in polite speech. This decline is attributed to the influence of Western culture, which has permeated Indonesia through technological advancements and television broadcasts showcasing urban and foreign cultures. The Javanese language, known for its unique *unggah-ungguh* (levels of politeness) and distinctive script, is one of the cultures at risk. The rapid development of technology, especially in education, necessitates its optimal utilization while preserving ancestral heritage such as the Javanese language. This study focuses on designing an optimal User Interface (UI) and User Experience (UX) for a Javanese language learning application on Android devices. The application includes features such as wulangan (lessons), pitakonan (questions), and tembang (traditional songs), with a focus on the User-Centered Design (UCD) approach. The research object is MI Nurul Islam, an elementary school in Brebes Regency. After the UI/UX design was successfully created, the System Usability Scale (SUS) was used to evaluate its effectiveness. The design received an average SUS score of 77.5, indicating that it is well-suited for further application development. The findings suggest that the designed application can significantly aid in preserving and promoting the use of the Javanese language among early childhood learners, addressing the decline caused by external cultural influences.